The Ins and Outs of Antigen Uptake in B cells - McShane, Adam Nathan; Malinova, Dessislava (Frontiers in Immunology, 2022)
Specific antigens induce B cell activation through the B cell receptor which initiated downstream signaling and undergoes endocytosis. While extensive research has shed light on the signaling pathways in health and disease, the endocytic mechanisms remain largely uncharacterized. Given the importance of BCR-antigen internalization for antigen presentation in initiating adaptive immune responses and its role in autoimmunity and malignancy, understanding the molecular mechanisms represents critical, and largely untapped, potential therapeutics. In this review, we discuss recent advancements in our understanding of BCR endocytic mechanisms and the role of the actin cytoskeleton and post-translational modifications in regulating BCR uptake. We discuss dysregulated BCR endocytosis in the context of B cell malignancies and autoimmune disorders. Finally, we pose several outstanding mechanistic questions which will critically advance our understanding of the coordination between BCR endocytosis and B cell activation.